Incidence and Prevalence Of Renal Dysfunction In Antiretroviral Therapy (ART) Naïve Patients Starting A Tenofovir (TDF) Based ART Regimen In Mitchell's Plain Community Health Centre (CHC) ARV Clinic - Fayanju, Olanrewaju Philips (Department of Public Health and Family Medicine, 2022)
Background: Tenofovir disoproxil fumarate (TDF) has high antiretrovirus (ARV) activity and available in fixed dose combination (FDC). However, it has been found to cause renal dysfunction. Objectives: To document the prevalence, incidence, pattern of occurence and associated factors of nephrotoxicity in patients initiated on TDF based ART regimen in Mitchell's Plain CHC ARV Clinic and make recommendations. Methodology: The study was conducted by reviewing retrospective records of all ARV naïve HIV positive adults initiated on TDF based ARV regimen from January 2016 to June 2016. The creatinine clearance (CrCl) was calculated from follow up parameters till June 2018. Results: 87 patients were included in the study and 56% were female. The mean age was 34 years. Majority, 83%, had normal renal function at ART initiation. Older age [OR = 1.11; 95% CI (1.03–1.19), p =0.005], was associated with an increased probability of non-normal renal function at baseline. The incidence of CrCl < 90ml/min were 1.5% at 1 month post ARV initiation, 3.3% at 4 months, 6.1% at 12 months and 2.8% at 24 months while the prevalence were 10.5%,11.5%, 20.4% and 16.7% respectively. Older age and male gender were independently associated with prevalence of renal impairment. Conclusion: Renal dysfunction in patients initiated on TDF based regimen in this study varied and were relatively small when compared to the prevalence of renal dysfunction at initiation. Majority of the decline in CrCl were transient and patients were found to have recovered after further follow up. It is recommended that the frequency of renal function monitoring in patients on TDF regimen be done within programmatic guidelines based on patients' risk factors and potential poor outcomes.